2020
DOI: 10.1002/jip.1557
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of question style and type in official Finnish asylum interview transcripts

Abstract: Interviews with asylum seekers are an important part of investigating the applicant's need of international protection. Few studies have examined if the questions used in interviews allow detailed and accurate narratives. In the current study, we analysed question style, question type, and question order from interviews of 80 official asylum cases realised by Finnish state authorities in 2017-2018. In accordance with best practise, questions were predominantly asked in an information-gathering style. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 32 publications
8
24
0
Order By: Relevance
“…Fourth, differences in the use of words and concepts, for example, different categorizations of relatives or different calendar systems, might increase misunderstandings (Granhag et al, 2017). Similar misunderstandings have been found in real‐life asylum interviews (Skrifvars et al, 2020; van Veldhuizen, 2017). Finally, officials continue to consider demeanour (e.g., non‐verbal cues such as eye contact and nodding) in their judgements, despite these cues’ unreliability as credibility indicators (Berg & Millbank, 2009; Herlihy & Turner, 2009).…”
Section: Commentary 3 Cultural Factors In Asylum Interviewingsupporting
confidence: 74%
See 1 more Smart Citation
“…Fourth, differences in the use of words and concepts, for example, different categorizations of relatives or different calendar systems, might increase misunderstandings (Granhag et al, 2017). Similar misunderstandings have been found in real‐life asylum interviews (Skrifvars et al, 2020; van Veldhuizen, 2017). Finally, officials continue to consider demeanour (e.g., non‐verbal cues such as eye contact and nodding) in their judgements, despite these cues’ unreliability as credibility indicators (Berg & Millbank, 2009; Herlihy & Turner, 2009).…”
Section: Commentary 3 Cultural Factors In Asylum Interviewingsupporting
confidence: 74%
“…Asylum officials might falsely perceive a narrative as untruthful if it does not meet the expected level of directness and emotional expressiveness. Third, recent findings indicate that asylum officials predominantly ask closed questions, despite best practice guidelines underlining the importance of open questions (Skrifvars et al, 2020; van Veldhuizen et al, 2018). This is especially problematic for applicants originating from collectivistic cultures that favour an implicit communication style, who may provide fewer details than Western officials expect (Gyulai, 2013).…”
Section: Commentary 3 Cultural Factors In Asylum Interviewingmentioning
confidence: 99%
“…To our knowledge, only two studies have investigated whether the type of questions officials ask allow asylum-seekers to provide accurate and elaborate statements. Analyzing a Finnish and a Dutch sample of asylum interview transcripts, the studies found that asylum officials asked predominantly closed questions (Skrifvars et al, 2020;van Veldhuizen et al, 2018). Only one report reviewed in the present study investigated the frequency of question types in interviews with sexual minorities.…”
Section: Interviewing Techniquesmentioning
confidence: 83%
“…The second strand has focused on parameters within the control of the asylum authority, or "system variables." These include the types of questions officials ask (e.g., Skrifvars et al, 2020), the accuracy of indicators used to assess the credibility of a claim (e.g., Maegherman et al, 2018), and the validity in testing applicants' knowledge of places to verify their provenance (van Veldhuizen et al, 2017). However, this body of research has focused on asylum decision-making in general and has so far overlooked the unique challenges related to specific types of asylum claims related to applicants' identities.…”
Section: The Need For Psychological Researchmentioning
confidence: 99%
“…Finally, both studies included qualitative observations, illustrating difficulties that asylum officials face in interviews, such as difficult questions, cultural differences and misunderstandings (Skrifvars et al, 2020; van Veldhuizen et al, 2018). A secondary aim of the current study was to further examine some of these difficulties more systematically.…”
Section: Introductionmentioning
confidence: 99%